2021
DOI: 10.1186/s12889-021-11713-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of fine particulate matter and ozone on non-accidental mortality and respiratory mortality in Lishui district, China

Abstract: Background In recent years, air pollution has become an imminent problem in China. Few studies have investigated the impact of air pollution on the mortality of the middle-aged and elderly people. Therefore, this study aims to evaluate the impact of PM2.5 (fine particulate matter) and O3 (ozone) on non-accidental mortality and respiratory mortality of the middle-aged and elderly people in Lishui District of Nanjing and provide the evidence for potential prevention and control measures of air po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…The reasons for higher estimated effects in females are complex and unclear. Some studies suggested that women are more susceptible to PM 2.5 because of greater airway responsiveness and differences in hormone levels. Some studies found that social factors in China, such as the education level of Chinese women being lower than that of men, may lead to more PM 2.5 exposure and greater mortality risk due to women’s lack of awareness of protection . At the same time, however, some studies have concluded the opposite. , The relevance of gender differences in physiology, workplace roles, and physical activity in epidemiological studies is complex.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for higher estimated effects in females are complex and unclear. Some studies suggested that women are more susceptible to PM 2.5 because of greater airway responsiveness and differences in hormone levels. Some studies found that social factors in China, such as the education level of Chinese women being lower than that of men, may lead to more PM 2.5 exposure and greater mortality risk due to women’s lack of awareness of protection . At the same time, however, some studies have concluded the opposite. , The relevance of gender differences in physiology, workplace roles, and physical activity in epidemiological studies is complex.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Filippini et al (2015), found childhood leukemia associated with higher traffic density. Chen et al (2021) showed that PM2.5, regardless of decrease in concentration is more harmful to human health than ozone. As previously reported (Bahino et al, 2018), atmospheric pollution of the Port Harcourt City is majorly ascribed to anthropogenic activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another recent study from Delhi, using data from 2010 to 2016, the increase in mortality due to PM 2.5 was greatest among those older than 60 years of age [23]. In a study conducted in Lishui district, China, shortterm mortality associated with O 3 and PM 2.5 was increased among both middle-aged and elderly [24].…”
Section: Introductionmentioning
confidence: 92%